Modelling, optimisation, and ultrasound pre-osmotic treatment of guava drying - Kek, Siok Peng (2012)
The drying behaviour and quality attributes of guava slices were investigated through modelling, optimisation, and ultrasound pre-osmotic conventional hot-air drying. Modelling studies of drying kinetics and quality attributes are presented using theoretical and statistical models by varying temperature from 55 to 75 °C and slice thickness from 3 to 9 mm. The quality of dried fruit was measured for its water activity, colour, vitamin C, and texture. The superposition technique with Midilli-Kucuk model showed efficiency in modelling the drying process with R2 = 0.9991. The second-order polynomial equations adequately described the quality of dried guava with regression coefficient, R2 > 0.7. Drying time was a good function of temperature and thickness (P < 0.001); water activity, colour, and vitamin C showed strong dependence on temperature (P < 0.1); while texture was mainly influenced by its thickness (P < 0.005). The optimum drying temperature of 70 °C at slice thickness of 6 mm was determined using the desirability function method. Simultaneous modelling using the theoretical and statistical drying models provides information on water diffusion and evaporation with the drying responses and factors. With the optimised slice thickness, 6 mm used in subsequent experiments, the effects of ultrasound pre-osmotic treatments on guava slices with indirect sonication using an ultrasonic bath system and direct sonication using an ultrasonic probe system were investigated. Pre-treatments in three osmotic solution concentrations of 0, 35,and 70 °Brix using ultrasonic bath at power from 0 – 2.5 kW for immersion time ranging for 20 – 40 minutes or using the ultrasonic probe at amplitude from 0 – 35% for immersion time of 6 – 20 minutes were investigated. Water loss, solid gain,weight reduction and colour change significantly increased (P < 0.0005) with ultrasound power or ultrasound amplitude, immersion time, and osmotic solution concentration. Indirect sonication with ultrasonic bath at 1.75 kW and 60 minutes of immersion time with 70 °Brix osmotic solution contributed to a highest water loss of 34.34%, solid gain of 8.85%, weight reduction of 24.17% and acceptable colour change when compared to the direct sonication with ultrasonic probe. The effect of optimum ultrasound pre-osmotic treatment at osmotic solution of 0, 35, and 70 °Brix prior to the hot-air drying at optimum drying temperature of 70 °C on the transport properties and quality attributes of dried guava was studied. The application of ultrasound pre-osmotic treatment prior to hot-air drying was able to reduce the drying time by 33.3%, increased the effective diffusivity by 34.5%,reduced the dried fruit colour changes by 37.9%, decreased the vitamin C contents by 32.5%, and resulted to the hardness of 430.1 g – 469.6 g, which was comparable to the fresh guava. The use of ultrasound in fruit drying is recommended to improve the drying process and the dried product quality.